Association between fear of hypoglycemia and physical activity in youth with type 1 diabetes: The SEARCH for diabetes in youth study. Issue 7 (18th August 2020) - Roberts, Alissa J.; Taplin, Craig E.; Isom, Scott; Divers, Jasmin; Saydah, Sharon; Jensen, Elizabeth T.; Mayer‐Davis, Elizabeth J.; Reid, Lauren A.; Liese, Angela D.; Dolan, Lawrence M.; Dabelea, Dana; Lawrence, Jean M.; et al.
Abstract: Background: Youth with type 1 diabetes (T1D) are encouraged to participate in physical activity (PA). Studies have identified fear of hypoglycemia (FOH) as a barrier to participating in PA. Objectives: To examine (a) PA patterns in youth with T1D by age group and (b) the relationship between both parental and youth FOH and youth PA. Methods: A cross‐sectional analysis from the SEARCH cohort study visit of youth ages 10 to 17 years with T1D (n = 1129) was conducted. Linear regression models estimated the association between self‐reported number of days of vigorous PA (VPA) and moderate PA (MPA) and both youth‐ and parent‐reported FOH. Multivariable models were adjusted for age, sex, race, duration of T1D, HbA1c, use of continuous glucose monitoring (CGM), recent severe hypoglycemia, primary insulin regimen, and BMI. Results: Participants were 52% female, had mean (sd) age 14.4 (4.2) years, diabetes duration 7.5 years (1.8), HbA1c 9.2% (1.7). Older youth were less likely to engage in VPA ( P < .01), or sports teams ( P < .01), but more likely to engage in MPA ( P < .01). Higher youth FOH (behavior subscale) was associated with increased levels of VPA (β (se) 0.30 (0.11), P = .01) but not significantly associated with MPA ( P = .06). There was no statistically significant association between parental FOH and youth PA. Conclusions: In SEARCH participants with T1D, VPA, and team sports participation declined with age, while MPA increased. We observed that higher scores on the youth FOH behavioral subscale were associated with increased VPA levels, suggesting that FOH may be less of a barrier to PA than previously thought.